Atomically Dispersed Molybdenum Catalysts for Efficient Ambient Nitrogen Fixation. Issue 8 (18th January 2019) - Han, Lili; Liu, Xijun; Chen, Jinping; Lin, Ruoqian; Liu, Haoxuan; Lü, Fang; Bak, Seongmin; Liang, Zhixiu; Zhao, Shunzheng; Stavitski, Eli; Luo, Jun; Adzic, Radoslav R.; et al.
Abstract: NH3 synthesis by the electrocatalytic N2 reduction reaction (NRR) under ambient conditions is an appealing alternative to the currently employed industrial method—the Haber–Bosch process—that requires high temperature and pressure. We report single Mo atoms anchored to nitrogen‐doped porous carbon as a cost‐effective catalyst for the NRR. Benefiting from the optimally high density of active sites and hierarchically porous carbon frameworks, this catalyst achieves a high NH3 yield rate (34.0±3.6 μg NH 3 h −1 mgcat. −1 ) and a high Faradaic efficiency (14.6±1.6 %) in 0.1 m KOH at room temperature. These values are considerably higher compared to previously reported non‐precious‐metal electrocatalysts. Moreover, this catalyst displays no obvious current drop during a 50 000 s NRR, and high activity and durability are achieved in 0.1 m HCl. The findings provide a promising lead for the design of efficient and robust single‐atom non‐precious‐metal catalysts for the electrocatalytic NRR. Abstract : Single molybdenum atoms anchored on nitrogen‐doped porous carbon were designed and synthesized for the electrocatalytic reduction of N2 to NH3 . The catalyst exhibited high electrocatalytic activity and stability, which is attributed to its structure, conductive carbon support, high porosity, and well‐dispersed single molybdenum atoms.